Family Interaction, Social Capital, and Trends in Time Use (FISCT), 1998-1999: (United States) - Robinson, John P. ([Verlag nicht ermittelbar], 2001)
For this project, data from 24-hour time diaries probing several indicators of social capital and life quality were gathered to update prior time series on how Americans spend time. Data were collected to be consistent with time-diary collections prepared in 1965, 1975, and 1985 (see ICPSR 7254, 7580, and 9875) to allow cross-time comparisons. The survey was conducted by the Survey Research Center at the University of Maryland between March 1998 and December 1999 (effectively covering each season of the year and each day of the week) with a representative sample of 1,151 respondents aged 18 and older. Using established time-diary procedures with Computer Assisted Telephone Interviewing (CATI), respondents were asked to complete "yesterday" time diaries detailing their primary activities from midnight to midnight of the previous day, their secondary activities (e.g., activities that occurred simultaneously with the primary activities), and when, with whom, and where they engaged in the activities. The project focus included the following substantive and methodological areas: (1) time spent in social interaction, particularly parental time with children, (2) measurement problems in time estimates, (3) activity and social interaction patterns of elderly Americans, and (4) time spent on the Internet and effects on social isolation and other media usage. In addition to the estimates of time use obtained from the time diaries, the project elicited information on (1) marital and parental status, education and employment status of the respondent and spouse (if married), age, race/ethnicity, and family income, (2) weekly and previous-day recall estimates of time spent on paid employment, housework, religious activities, and television viewing, (3) feelings of time pressure, and (4) use of the Internet, e-mail, and home computers.